Meeting of the expert committee on the use of pre-mixed insulin preparation Humalog Mix 50 in type 2 diabetes mellitus - Editorial team Diabetes Mellitus (Endocrinology Research Centre, 2013)
The panel of experts has a held a discussion on effectiveness and tactics of glycemic control by pre-mixed insulin preparations in T2DM. Special attention was paid to the aspects of treatment with Humalog Mix 50, including indications and contraindications, potential for the achievement of therapeutic goals and optimization of patient monitoring.